PENGEMBANGAN BAHAN AJAR DIGITAL BERBANTUAN HEYZINE FLIPBOOK PADA MATERI TEKS EKSPOSISI SISWA KELAS V SDN PANARAGAN 1 BOGOR - Sabrina Murtafiah, Putri; Sandi Budiana; Fitri Anjaswuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Development of Digital Teaching Materials Assisted by Heyzine flipbook on Exposition Text Material. This type of research is a Research and Development (R&D)development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation)..This study aims to develop, test the feasibility and test the effectiveness of the product. This research was conducted at SDN Panaragan 1 Bogor City in class V-B with 30 students in the even semester of 2024/2025. This research conducted a needs Analysis by making observation instrument sheets, interviews, questionnaire assessments from material experts, linguists, media experts, teacher response questionnaires and student response questionnaires. The results showed that digital teaching materials assisted by heyzine flipbook based on the average validation assessment of material experts obtained a percentage of 96%, linguists at 98%, media experts at 94% which was included in the ‘very feasible’ category. The results of the student response questionnaire obtained 92% in the “very good” category and the average N-Gain score obtained 0.72 in the moderate category. Based on the above results, it shows that the development of digital teaching materials assisted by heyzine flipbook on exposition text material is declared “very feasible” and “very good” to be used in the learning process.